Effect of Banisteriopsis caapi and Psychotria viridis “ayahuasca Binomio” ingestion in the rat brain hippocampus - Castro, Américo (2016)
Objective. To assess the effect of Banisteriopsis caapi and Psychotria viridis ‘binomio ayahuasca’ ingestion in rat hippocampus. Design. Experimental, descriptive, analytical, and cross-sectional study. Institution. Research Institute of Pharmaceutical Sciences and Natural Resources, Faculty of Pharmacy and Biochemistry, Universidad Nacional Mayor de San Marcos, Lima, Peru. Biological material. Rats. Interventions. Orogastric administration of ‘binomio ayahuasca’ in adult Rattus norvegicus albinus Holtzman strain. Seven groups of five animals with an average weight of 240 ± 30 g were administered: (GI) placebo, (GII) 2.5 mL of diazepam (GIII) 0.7 mL of Banisteriopsis caapi solution, (GIV) 0,7 mL of Psychotria viridis solution. Groups GV, GVI and GVII received 0.7 mL, 3.5 mL and 7.0 mL of binomio ayahuasca solution, respectively. Main outcome measures. Macroscopically: reflex movements and motor skills. Microscopically: amount of pyramidal and granulose cells, cell disorganization. Results. The phytochemical screening of the extract showed alkaloids, anthraquinones, triterpenoids and steroids, phenols, flavonoids and saponins. The group administered with 0.7 mL of binomio (GV) had a significant increase in the number of granule cells over pyramidal cells. The group administered with 3.5 mL of binomio (GVI) had less granule cells and large and small pyramidal cells. The group administered with 7.0 mL of binomio (CVII) had cell disorganization, large and small pyramidal cells and an increase in granule cells. Conclusions. The alcoholic extract of binomio ayahuasca showed a neuropathological effect on rat brain hippocampus.